Cloning of mouse integrin alphaV cDNA and role of the alphaV-related matrix receptors in metanephric development (The Rockefeller University Press, 1996)
Metanephrogenesis has been a long-standing model to study cell-matrix interactions. A number of adhesion molecules, including matrix receptors (i.e., integrins), are believed to be involved in such interactions. The integrins contain alpha and beta s ubunits and are present in various tissues in different heterodimeric forms. In this study, one of the members of the integrin superfamily, alphaV, was characterized, and its relevance in murine nephrogenesis was investigated. Mouse embryonic renal cDNA libraries were prepared and screened for alphaV, and multiple clones were isolated and sequenced. The deduced amino acid sequence of the alpha-v cDNA clones and hydropathic analysis revealed that it has a typical signal sequence and extracellular, transmembrane, and cytoplasmic domains, with multiple Ca2+ binding sites. No A(U)nA mRNA instability motifs were present. Conformational analysis revealed no rigid long-range-ordered structure in murine alphaV. The alphaV was expressed in the embryonic kidney at day 13 of the gestation, with a transcript size of approximately 7 kb. Its expression increased progressively during the later gestational stages and in the neonatal period. It was distributed in the epithelial elements of developing nephrons and was absent in the uninduced mesenchyme. In mature metanephroi, the expression was relatively high in the glomeruli and blood vessels, as compared to the tubules. Various heterodimeric associations of alphaV, i.e., with beta1, beta3, beta5, and beta6, were observed in metanephric tissues. Inclusion of alphaV- antisense-oligodeoxynucleotide or -antibody in metanephric culture induced dysmorphogenesis of the kidney with reduced population of the nephrons, disorganization of the ureteric bud branches, and reduction of mRNA and protein expressions of alphaV. The expressions of integrin beta3, beta5, and beta6 were unaltered. These findings suggest that the integrin alphaV is developmentally regulated, has a distinct spatio- temporal expression, and is relevant in the mammalian organogenesis.